Improving Student Learning Outcomes through the Discovery Learning Model in Islamic Cultural History Learning at MI Darul Ma'arif Pingaran Ulu - Kamsiah; Jumiati (MANDAILING GLOBAL EDUKASIA, 2025)
The purpose of this study was to determine the application and learning outcomes of the Discovery Learning learning model in class V MI Darul Ma'arif Pingaran Ulu. The formulation of the problem in this study is how is the application of the Discovery Learning model in SKI learning in class V MI Darul Ma'arif Pingaran Ulu? How are the activities and learning outcomes of the application of the Discovery Learning model in SKI learning in class V MI Darul Ma'arif Pingaran Ulu? This study is a classroom action research (CAR) using qualitative descriptive data analysis, namely by analyzing student development data from cycle I to cycle II. The subjects of this study were 13 students in class V MI Darul Ma'arif Pingaran Ulu. Data collection techniques through test and observation methods obtained from each action. From the analysis of cycle I data, it shows that the learning outcomes have met the minimum completion criteria (KKM) which is 70, this can be seen from the achievement of group test scores for students in cycle I <70 as many as 5 people (38%) and students who obtained scores >70 as many as 8 people (62%) with a class average of 74.2. In the independent test, students who obtained scores <70 were 5 people (38%) and students who obtained scores >70 were 8 people (62%) with a class average of 72, while the group test scores in cycle II all students obtained scores >70 (100%) with a class average of 80.5. In the independent test, students who obtained scores <70 were 2 people (15%), while those who obtained scores >70 were 11 people (85%) with a class average of 77.5. In cycle II, student learning outcomes increased with a completion percentage of 100% (group) and 85% (independent). The learning activities of class V MI Darul Ma'arif students in both social and skill aspects increased. This can be seen in the observation score of cycle I in the social aspect, where 7 students (54%) obtained an A or B and 6 students (46%) obtained a C or D. Meanwhile, the social activity score in cycle II all students obtained an A or B (100%). This social activity increased by 46%. Meanwhile, in the skill aspect in cycle I, only 46% of students obtained completion, but in cycle II 92% of students obtained completion, so it can be concluded that this skill activity increased by 46% from before. Thus, it can be concluded that the application of the Discovery Learning learning model can increase student activity and learning outcomes.